Rules of origin in international trade / Stefano Inama. - Inama, Stefano (Cambridge University Press, 2022)
This book provides comprehensive, in-depth analysis of the different sets of rules of origin adopted by major trading partners and worldwide, as well as efforts to establish multilateral rules at WTO and WCO. It discusses the status of non-preferential as well as preferential rules of origin in international trade, their evolution during the last decades and their tendencies and future. With its multidisciplinary approach, this book's contents provide comparative analysis of the relevant legal and economic features of different rules origin compilation sets, reviewing their drafting differences and their implications and impact on the economic and industrial environments. This edition has been updated and expanded to include the latest developments on rules of origin at multilateral level in WTO and WCO and on rules of origin in recent FTAs. Drawing from his thirty years of experience, Stefano Inama provides insights from trade negotiations along with practical tools for policy makers and practitioners, orientation for the private sector and analytical tools for researchers.